2021
DOI: 10.3390/cells10020332
|View full text |Cite
|
Sign up to set email alerts
|

Brassinin Inhibits Proliferation in Human Liver Cancer Cells via Mitochondrial Dysfunction

Abstract: Brassinin is a phytochemical derived from Chinese cabbage, a cruciferous vegetable. Brassinin has shown anticancer effects on prostate and colon cancer cells, among others. However, its mechanisms and effects on hepatocellular carcinoma (HCC) have not been elucidated yet. Our results confirmed that brassinin exerted antiproliferative effects by reducing proliferating cell nuclear antigen (PCNA) activity, a proliferation indicator and inducing cell cycle arrest in human HCC (Huh7 and Hep3B) cells. Brassinin als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…It has been a very well proven fact that mitochondria play a very pivotal role in intrinsic apoptotic pathway (Davidson et al., 2020; Peña‐Blanco & García‐Sáez, 2018). Intracellular ROS generation can damage biological macromolecules, lipid membrane, leading to protein denaturation (Hong et al., 2021; Kiskova et al., 2020). These events initiate the intrinsic apoptotic pathway (D'Onofrio et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It has been a very well proven fact that mitochondria play a very pivotal role in intrinsic apoptotic pathway (Davidson et al., 2020; Peña‐Blanco & García‐Sáez, 2018). Intracellular ROS generation can damage biological macromolecules, lipid membrane, leading to protein denaturation (Hong et al., 2021; Kiskova et al., 2020). These events initiate the intrinsic apoptotic pathway (D'Onofrio et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported an anti-cancer activity of brassinin on several types of cancer, including colon [ 3 ], liver [ 4 ], prostate [ 24 ], and lung cancer [ 5 , 25 ]. However, the effects of brassinin on TNBC development have not been reported so far.…”
Section: Discussionmentioning
confidence: 99%
“…Such a compound is brassinin, a phytoalexin isolated from cruciferous vegetables, including cabbage, broccoli, and mustard greens [ 1 ]. Previous in-vitro studies demonstrated anti-proliferative and cytotoxic effects of brassinin on human colorectal [ 2 , 3 ], liver [ 4 ], and lung cancer cells [ 5 ]. In addition, brassinin has been shown to enhance the anti-cancer effects of paclitaxel in a A549 lung cancer xenograft mouse model [ 5 ] and an autochthonous mouse model of mammary gland tumors [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alpinumisoflavone (50 µM) or DMSO-treated cell suspensions were seeded to the lids of culture dishes and maintained for 72 h for imaging purposes. The ImageJ software was used for analysis of the spheroid surface [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Lastly, after several washing steps, the nuclei were labeled with 5 µg/mL 4′, 6-diamidino-2-phenylindole (DAPI). The images were acquired using a confocal microscope (LSM710, Carl Zeiss, Oberkochen, Germany) [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%